IMPROVING STUDENTS' MATHEMATICAL UNDERSTANDING AND PROBLEM SOLVING SKILLS AND THEIR LEARNING INTERESTS IN MTS THROUGH CONTEXTUAL TEACHING AND LEARNING LEARNING (CTL) - Yustinawati, Rina; Sabandar, Jozua ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This article is derived from the results of research entitled "Improving Students' Mathematical Understanding and Problem Solving Skills and Their Learning Interests in MTs through Contextual Teaching and Learning Learning (CTL)" which aims to see not only the influence of Contextual Teaching and Learning (CTL) in increasing students' mathematical understanding and problems solving skills, but also to see their interests in learning mathematic as well. This research is a quasi-experiment study. The population in this study is all students of MTs Cianjur district. The sample in this research are 36 students of class VII A as experiment class and 36 students of class VII B as control class. The data in this study was analyzed using parametric and non parametric statistics. The results of this study indicate that students' mathematical understanding and problem solving skills, as well as their learning interests when using the approach of Contextual Teaching and Learning Learning (CTL), is better than the students using conventional learning. There is an association between the quality of students' mathematical understanding skill and their mathematical problem solving skill with high enough criteria. There is an association between the quality of students' understanding and their interest in learning mathematic with high criteria. There is an association between students' problem-solving skill and learning interests with fairly high criteria.